EFFECT OF SHARIA INTERBANK MUDHARABAH INVESTMENT CERTIFICATE (SIMA) ON THE MONEY SUPPLY (JUB) IN 2014-2018 - putri sara; adanan murrah; indah sari (Institut Agama Islam Negeri Padangsidimpuan, 2022)
There is almost no part of human economic life that is not related to the existence of money. Excessive increases in the money supply can drive price increases beyond expected levels so that in the long run it can disrupt economic growth. Conversely, if an increase in the money supply is low, economic devastation will occur. Sharia Interbank Mudharabah Investment Certificate (SIMA) is a tool used for transactions in the Sharia Interbank Money Market (PUAS). This certificate is a certificate that is used as an investment tool for banks with excess funds to make a profit, and on the other hand, the Interbank Sharia Mudharabah Investment Certificate (SIMA) is also a means for banks experiencing shortages of funds to obtain short-term funds on the mudharabah principle. The theory used is the theory relating to the Sharia Interbank Mudharabah Investment Certificate (SIMA), the Amount of Money Supply (JUB), and the theories that support this research. The method used in this study was started by obtaining data using documentation techniques through the official website of Bank Indonesia, www.bi.go.id, and the official website of the Financial Services Authority, www.ojk.go.id. Then processed with the help of SPSS Version 23. The test used to prove the hypothesis is a partial test (t test) and the coefficient of determination (R2). Partial test results (t-test) can be concluded that the variable Interbank Sharia Mudharabah Investment Certificate (SIMA) affects the Amount of Money Supply (JUB), seen from the tcount t table = 1.67655. Based on the Adjusted R square value of 0.490 or 49% this shows that the variable Interbank Sharia Mudharabah Investment Certificate (SIMA) affects the variable Amount of Money Supply (JUB). While the remaining 51% is influenced by other variables not discussed in this study.